comparative study between Juvenile and adult psoriaticarthropathy in rnosul area - F. Al-jumaily , Abdullah (Tikrit Journal of Pharmaceutical Sciences, 2023)
Psoriasis is anon-infectious,chronic disease of the skin. Arthritis associated in various age groups. This study used to evaluates difference between juvenile and adult psoriatic arthropathy at Mosul city, Mosul teaching hospital during the period of 1 st Jan. till 3o1h of June 2002. 115 patients with psoriasis participated in this study, 80 of them more than 16 years old consist of 41.9% male and 58.1% female with mean age ±SD = 38.6 ± 15.3, while other 35 patients less than 16 years old consist of 60% male and 40% female with mean age± SD = 9.2 (4-16). Arthritis associated, followed or antedated skin lesions, in 20% of them nails were affected, only 20% of juvenile patients and about 80.5% of adult patients were complaint of morning stiffness and only I 0.5% of adult patients developed ocular involvements in form of iritis. Family association of psoriasis and or psoriatic arthritis were presents in both juvenile and adult patients with psoriatic arthritis.